The difference in under-expenditure of the social welfare budget in Korea - Lee, Young (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2015)
This research investigates the relationship between under-expenditure of the social welfare budget within a limited budget and the determinants that have an effect on them. Relationships and determinants between under-expenditure of the social welfare budget have generally received relatively little attention from academics. The aim of this article is to examine the differences in the under- expenditures of the social welfare budget in the Korea between 1965 and 2008. It is shown that public assistance and social service expenditures are not comparable with national insurance expenditure according to the Box-Jenkins’ multi-variant ARIMA models. The appearance of them being commensurate is spurious because it is affected by political economic factors. The research findings in this paper can contribute to the development of budgetary theory and budgetary politics. However some findings within in the ARIMA models were incapable of being interpreted within existing theories and conjecture such as those with a 9 year time lag, etc. Further studies are therefore required.

Przedmiotem badania jest relacja między wydatkami niekwalifikowanym budżetu pomocy społecznej w ramach ograniczonego budżetu Korei w okresie 1965–2008.W artykule wskazano, że pomoc publiczna i wydatki na usługi społeczne są nie do porównania z wydatkami ubezpieczenia narodowego zgodnie z wielowariantowymi modelami ARIMA Box-Jenkins. Ich obecność poddana współmierności jest fałszywa ze względu na wpływ czynników polityczno-gospodarczych. Rezultaty badania w tym artykule mogą wnieść wkład w rozwój teorii budżetowej i polityk budżetowych. Jednak niektóre rezultaty badań powstałych w oparciu o modele ARIMA mogły być nieadekwatne do poddania interpretacji w ramach istniejących teorii i formułują przypuszczenia takie jak te z dziewięcioletnim opóźnieniem, etc. W związku z tym dalsze badania są konieczne.
Różnica w wydatkach niekwalifikowanych budżetu pomocy społecznej w Korei
Keywords: social welfare budget; multi-variant ARIMA model; budżet pomocy społecznej; wielowariantowy model ARIMA